2009
DOI: 10.1029/2009gl038163
|View full text |Cite
|
Sign up to set email alerts
|

Thermal phase curves observed in Saturn's main rings by Cassini‐CIRS: Detection of an opposition effect?

Abstract: We report on thermal phase curve measurements of Saturn's main rings by the CIRS infrared spectrometer on‐board the CASSINI spacecraft. The extensive data set acquired by Cassini since its insertion in orbit around Saturn provides for the first time spatially resolved temperature measurements over broad phase angle ranges and for different solar elevations. Each of these curves exhibit a nonlinear variation in temperature with phase angle, with pronounced surges at medium to low phase angles that we interpret … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…Independent support for the interparticle shadowing opposition effect is provided by the Cassini CIRS measurements, showing a pronounced opposition effect in the ring's thermal phase curves (Altobelli et al 2009). CB is ruled out, since there can be no interference between the incoming visual photons heating the particle and the infrared photons reradiating the heat.…”
Section: Discussionmentioning
confidence: 93%
“…Independent support for the interparticle shadowing opposition effect is provided by the Cassini CIRS measurements, showing a pronounced opposition effect in the ring's thermal phase curves (Altobelli et al 2009). CB is ruled out, since there can be no interference between the incoming visual photons heating the particle and the infrared photons reradiating the heat.…”
Section: Discussionmentioning
confidence: 93%
“…One puzzle from previous CIRS studies is the discrepancy between the narrow surge found by Altobelli et al (2007) and the broad surge found by Altobelli et al (2009). There are several ways to understand why these two studies did not provide the same values for the thermal surge width.…”
Section: Narrow Surge Versus Broad Surgementioning
confidence: 94%
“…• 03. However, there is still a debate on whether or not the ring thermal surge is narrow (less than a degree) or broad (several tens of degrees), see Wallis et al (2005Wallis et al ( , 2006 and Altobelli et al (2007Altobelli et al ( , 2009. This is particularly important because the thermal surge width was used in Altobelli et al (2007Altobelli et al ( , 2009) to derive ring properties.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is more appropriate to calculate the mean temperature by integrating the thermal flux over the solid angle as done in Pilorz et al (2014) for the B ring. Nevertheless, since the A ring shows relatively weak phase dependences (Altobelli et al, 2009), this simple removal of low phase data has only a minor effect. For |B ′ | > 2 • , we also remove data near Saturn's shadow as the temperatures in the shadow are much lower than those around the noon.…”
Section: Data Selectionmentioning
confidence: 99%